Association of low birth weight with beta cell function in the adult first degree relatives of non-insulin dependent diabetic subjects. - Cook, J; Levy, J; Page, R; Shaw, J; Hattersley, A; Turner, R (1993)
OBJECTIVE: To examine the relation between birth weight and beta cell function in the first degree relatives of non-insulin dependent diabetic subjects. DESIGN: Cross sectional study of 101 adults of known birth weight from 47 families which had at least one member with non-insulin dependent diabetes. SUBJECTS: 101 white adults aged mean 43 (SD 7) years. SETTING: Oxfordshire, England. MAIN OUTCOME MEASURES: Glucose tolerance was measured by continuous infusion glucose tolerance test. beta cell function and insulin sensitivity were calculated from the fasting plasma glucose and insulin concentrations with homeostasis model assessment. beta cell function was standardised to allow for the confounding effects of age and obesity. RESULTS: Twenty seven subjects had non-insulin dependent diabetes, 32 had impaired glucose tolerance, and 42 were normoglycaemic. Birth weight correlated with the beta cell function of the complete cohort (rs = 0.29, p = 0.005), the non-insulin dependent diabetic subjects (rs = 0.50, p = 0.023), and the non-diabetic subjects (rs = 0.29, p = 0.013). The non-insulin dependent diabetic (n = 27) and the non-diabetic (n = 74) subjects had similar mean (inter-quartile range) centile birth weight 50% (19%-91%), and 53% (30%-75%) respectively. Non-insulin dependent diabetic subjects had significantly lower beta function than the non-diabetic subjects: 69% (48%-83%) v 97% (86%-120%), p < 0.001. CONCLUSIONS: The cause of the association between low birth weight and reduced beta cell function in adult life is uncertain. Impaired beta cell function in non-insulin dependent diabetic subjects was not accounted for by low birth weight, and genetic or environmental factors are likely to be necessary for development of diabetes.